Attenuating Property OF Delonix elata Plant Against Inhibition of Acetylcholinesterase Due to Cypermethrin Toxicity on Fresh Water Fish Cyprinus carpio Linn - Pugazhendy, K (International Journal of Pharmaceutical & Biological Archive, 2012)
Attenuating Property OF Delonix elata Plant Against Inhibition of Acetylcholinesterase Due to Cypermethrin Toxicity on Fresh Water Fish Cyprinus carpio Linn